Answer:
the 3rd one
Step-by-step explanation:
Let's solve this system of equations through substitution.
We have these two equations.
-7x-2y=14
6x+6y=18
Now let divide the second equation by 6.
6x+6y=18 ----> x+y=3
Next, let us move y to the right side of the equation.
x+y=3 -------> x=3-y (x equals 3-y)
Because we found out that what x is in terms of y, we can input that in for every instance of x in this equation below.
-7x-2y=14 becomes -7(3-y)-2y=14 (Why? Because x equals 3-y!)
We have a one variable equation now and can solve for y.
-7(3-y)-2y=14
-21+7y-2y=14
5y=35
y=7
Plug in 7 for y in any equation to find x.
x+y=3
x+7=3
x=-4
answer: x=-4, y=7
Answer:
145
Step-by-step explanation:
x = 2 , y= 5
Putting the values of x and y in the expression
=3(2) (5)^2-5
=3(2)(25)-5
=150 -5
=145
Answer: i'm pretty sure it's 38,500
Step-by-step explanation:
Answer:
Step-by-step explanation:
the 2nd one
x l y
1 l 2
2 l 4
3 l 8
4 l 16